Indeks Kepuasan Kerja Dosen dan Karyawan Non Akademik Institut Informatika dan Bisnis Darmajaya - Stefanus Rumangkit; Anggawidia Wibaselpa (Jurnal Bisnis Darmajaya, 2020)
This study aims to investigate job satisfaction of lecturers and non-academic employees of the Darmajaya Institute of Informatics and Business. This research is descriptive research. To measure job satisfaction, the instrument used was a job satisfaction survey (JSS) developed by Spector (1994) consisting of 36 questions. The respondents in this study were 155 lecturers and non-academic employees. The data analysis tool used the Employee Satisfaction Index. The results of the investigation showed that the level of job satisfaction of lecturers and non-academic employees on salaries, promotions, supervision, awards, operational procedures, work colleagues, nature of work, and communication were at very satisfied levels. However, when viewed from the aspect of profit, employee satisfaction is at the level of satisfaction. This finding also strengthens the instrument suitability test for the job satisfaction survey measuring instrument developed by Spector. In addition, this finding also reinforces the two-factor theory developed by Herzberg, that salary, promotion, supervision, rewards, benefits, operational procedures, work colleagues, nature of work, and communication are antecedents of job satisfaction.Keywords —Job Satisfaction, Job Satisfaction Survei, Two Factor Theory, Lecturer